2005
DOI: 10.1021/ol0508126
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of the Proposed Structure for Pyragonicin

Abstract: [structure: see text] The total synthesis of acetogenin 1 reported for pyragonicin and its 10-epimer 32 is described. The common THP ring system was stereoselectively constructed through a SmI(2)-induced reductive cyclization of beta-alkoxy acrylate 5 followed by Mitsunobu inversion, and each chiral center at C-10 was created by Brown's asymmetric allylation. Compound 1 had spectroscopic data consistent with that of natural pyragonicin, but a different optical rotation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 36 publications
2
29
0
Order By: Relevance
“…In the event, exposure to SmI 2 provided the desired pyran 12 in 69% yield for the three steps. The relative stereochemistry of 12 was assigned by NMR and nOe analysis, and in agreement with literature precedent 5-10…”
supporting
confidence: 87%
“…In the event, exposure to SmI 2 provided the desired pyran 12 in 69% yield for the three steps. The relative stereochemistry of 12 was assigned by NMR and nOe analysis, and in agreement with literature precedent 5-10…”
supporting
confidence: 87%
“…Carbon-carbon double bond or triple bond reduction using Wilkinson's catalyst were used in synthesis of 10-hydroxyasimicin [323], murisolins [324], tuberostemonines [688], eupomatilones [211], guanacastepene A [942], pyragonicin [943], mucocin [944], 3-hydroxy-4-methyl-2-tetradecyl-4-butenolide [945], gleenol and axeenol [946], (−)-jimenezin [947], epi-(+)-SCH-642305 [948], methionine aminopeptidase-2-inhibitor [949] and the tricyclic core of cyathin diterpenoids [455]. Crabtree's iridium catalyst was used in synthesis of prodigiosines [198], batzelladine alkaloids (Eq.…”
Section: Formation Of Carbon-hydrogen Bonds From Alkenes Alkynes Camentioning
confidence: 99%
“…however, research on the inhibition of acetogenins against pol and topo activities is limited, probably due to the small quantities of natural products. Since the total synthesis of bioactive acetogenins, such as compound 5, is possible (17)(18)(19)(20)(21)(22)(23)(24)(25), these compounds should be provided and studied in pharmaceutical research throughout the world. compound 5 directly inhibited animal pol and human topo activities (table ii), but did not bind to dna.…”
Section: Discussionmentioning
confidence: 99%
“…1) was achieved (17)(18)(19)(20)(21)(22)(23)(24)(25). Since mclaughlin et al and mata et al reported that some acetogenins have cytotoxicity against human cancer cell lines (4-7), the purpose of this review is to investigate the biochemical action of the compounds against dna metabolic enzymes such as pols and topos, and to use the compound as an antineoplastic agent.…”
Section: Introductionmentioning
confidence: 99%